2007
DOI: 10.1007/s10533-007-9145-8
|View full text |Cite
|
Sign up to set email alerts
|

The flux of carbon from rivers: the case for flux from England and Wales

Abstract: This study uses the extensive monitoring datasets of the Environment Agency of England and Wales to calculate the flux of dissolved organic carbon (DOC); particulate organic carbon (POC); and excess dissolved CO 2 through English and Welsh rivers. The innovation of this study's approach is to account for the losses of carbon within the fluvial system as well as fluxes at the catchment outlet. In order to make this assessment this study considers: the biochemical oxygen demand (BOD) as a measure of the degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
3
33
4
Order By: Relevance
“…If all DOC is converted to CO 2 the flux estimate ranges from 6.7-18.9 g cm −2 yr −1 across the catchments. This is larger than CO 2 efflux measured directly by at Auchencorth Moss, 4.6 g C m −2 yr −1 or the estimated average of 4.1 g C cm −2 yr −1 for the rivers of England and Wales (Worrall et al, 2007), but smaller than the measured efflux of 35.8 g cm −2 yr −1 from rivers in the NE European tundra (measured only during the ice free period) considered to have come from the respiration of organic matter and free CO 2 leached from the catchment (Heikkinen et al, 2004). It is likely that our estimate for potential CO 2 efflux based on stoichiometric excess is greater than that effluxed from the system as not all DOC will be respired prior to export from the catchment.…”
Section: The Interaction Between Doc and Nutrient Exportcontrasting
confidence: 57%
“…If all DOC is converted to CO 2 the flux estimate ranges from 6.7-18.9 g cm −2 yr −1 across the catchments. This is larger than CO 2 efflux measured directly by at Auchencorth Moss, 4.6 g C m −2 yr −1 or the estimated average of 4.1 g C cm −2 yr −1 for the rivers of England and Wales (Worrall et al, 2007), but smaller than the measured efflux of 35.8 g cm −2 yr −1 from rivers in the NE European tundra (measured only during the ice free period) considered to have come from the respiration of organic matter and free CO 2 leached from the catchment (Heikkinen et al, 2004). It is likely that our estimate for potential CO 2 efflux based on stoichiometric excess is greater than that effluxed from the system as not all DOC will be respired prior to export from the catchment.…”
Section: The Interaction Between Doc and Nutrient Exportcontrasting
confidence: 57%
“…Several studies have shown that in-stream production of DOC (for example from POC degradation) is small in comparison to that which is derived from terrestrial sources (e.g. Worrall et al, 2007).…”
Section: Docmentioning
confidence: 99%
“…Significant increases in DOC concentrations in runoff from upland peat catchments have been observed over the past few decades (Worrall et al, 2003;Worrall et al, 2004;Evans et al, 2005;Evans et al, 2006;Worrall and Burt, 2007). Numerous mechanisms have been suggested to account for these increases (Evans et al, 2005;Worrall et al, 2007b) including land management change, decreases in sulphate deposition, and temperature change. The presence of DOC results in water becoming coloured, posing * Correspondence to: Richard Grayson, School of Geography, University of Leeds, Leeds, LS2 9JT, UK.…”
Section: Introductionmentioning
confidence: 99%
“…Most scientific studies involve absolute measurements of DOC (using TOC analysers) to establish the relationship between absorbance and DOC. Several studies reporting increased DOC losses from UK upland peat catchments have used absorbance at 400 nm as a proxy for DOC (Watts et al, 2001;Worrall et al, 2003Worrall et al, , 2007b. In addition to direct measurement of DOC the UK Environmental Change Network (ECN) measure absorbance at 436 nm, with Worrall et al (2002) having observed a strong linear relationship between DOC and absorbance at both 436 and 400 nm.…”
Section: Introductionmentioning
confidence: 99%